Comportamiento de componentes agronómicos y de rendimiento bajo dosis creciente de gallinaza en Allium cepa L. var. agregatum "cebolla regional", en Zungarococha-Loreto. 2021 - Mozombite Paitamala, Laleska Malu (2022)
The experiment "Behavior of agronomic and yield components under increasing dose of chicken in Allium strain L. var. agregatum "regional onion", in Zungarococha-Loreto. 2021", was held at the facilities of the Workshop on Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located at Km. 3 of the road to Zungarococha. The type of research was experimental, explanatory with one independent variable (increasing dose of chicken) and nine dependent variables (plant height, plant diameter, number of leaves/plant, leaf/plant weight, bulb diameter, total plant weight, number of bulbs/plant, weight of bulbs/plant and weight of bulbs/ha). The objective of the research work was to determine the behavior of the agronomic and yield components under increasing dose of chicken in Allium strain L. var agregatum "regional onion", in Zungarococha-Loreto. 2021. The experimental design that was used was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 4 rows, 10 plants/row and the sampling unit consisted of four plants/experimental unit. At the end of the experiment we had the following conclusions: The increasing doses of chicken influenced the agronomic behavior and yield of the crop of Allium strain L. var. agregatum "regional onion, where the T4 Treatment (60 t of chicken /ha), presented the best agronomic behavior and crop yield; the T4 Treatment (60 t of chicken/ha) presented the best yield of bulb weight/ha, with 9,262.5 Kg and the T4 Treatment (60 t of hen/ha) presented the best economic benefit, with a utility of S/.21,342.00.